Self-propelled motion switching in nematic liquid crystal droplets in aqueous surfactant solutions - Suga, Mariko; Suda, Saori; Ichikawa, Masatoshi; Kimura, Yasuyuki (Physical review. E, 2018)
The self-propelled motions of micron-sized nematic liquid crystal droplets in an aqueous surfactant solution have been studied by tracking individual droplets over long time periods. Switching between self-propelled modes is observed as the droplet size decreases at a nearly constant dissolution rate: from random to helical and then straight motion. The velocity of the droplet decreases with its size for straight and helical motions but is independent of size for random motion. The switching between helical and straight motions is found to be governed by the self-propelled velocity, and is confirmed by experiments at various surfactant concentrations. The helical motion appears along with a shifting of a point defect from the self-propelled direction of the droplet. The critical velocity for this shift of the defect position is found to be related with the Ericksen number, which is defined by the ratio of the viscous and elastic stresses. In a thin cell whose thickness is smaller than that of the initial droplet size, the droplets show more complex trajectories, including "figure-8s" and zigzags. The appearance of those characteristic motions is attributed to autochemotaxis of the droplet.